Analysis of Urban Thermal Environment Effect by TIRS and GIS: A Case Study of Zhuhai, Guangdong - Zhang, Tingjun; Wang, Ruei-Yuan; Wang, Zhe Zhu Yun-Shang (International Journal of Environment, Agriculture and Biotechnology, 2023)
The rapid development of urbanization in China is not only reflected in the tight land area and rapid population growth but also causes changes in the local urban climate, such as the increasingly obvious urban heat island effect (UHIE). This study explores the impact of urban surface cover types on the urban thermal environment. Taking Zhuhai City, Guangdong Province as an example, based on Landsat-8 thermal infrared remote sensing (TIRS) data, the atmospheric correction method (also known as Radiation Transfer Equation, RTE) and spilt-window inversion algorithm are used to invert the land surface temperature (LST) of the study area and compare their accuracy. After applying ArcGIS to normalize the data, the standard deviation method was used to classify the LST and obtain the distribution map of surface temperature levels in the urban area. In addition, the urban heat island proportion index was used to evaluate the UHIE in the study area, and the distribution of UHIE intensity was obtained. Based on geographical and national data, a combination of mathematical and spatial statistics was used to establish a correlation between the proportion of underlying surface coverage and LST in three different types of water bodies: vegetation and impermeable water surfaces. The results of the effect of urban underlying surface layout on the thermal environment were obtained, and the overall thermal environment effect of the city was obtained.